How long should antipsychotic treatment be continued after a single episode of schizophrenia?. Issue 3 (May 2016) - Emsley, Robin; Kilian, Sanja; Phahladira, Lebogang
Abstract : Purpose of review: In this article, recent publications addressing the pros and cons of antipsychotic maintenance treatment are reviewed and some recommendations formulated. Recent findings: On one hand, relapse rates are extremely high when antipsychotic treatment is discontinued, even after a single episode of psychosis; there are no reliable predictors of relapse; and there are serious psychosocial and biological consequences of relapse. On the other hand, in addition to the well recognised side-effect burden of antipsychotics, a few recent publications suggest an association between greater exposure to antipsychotic treatment and poorer long-term outcome. Summary: There is more evidence in favour of maintaining patients on antipsychotics than on stopping them. There is an urgent need for more and better research before the question of duration of maintenance after a single episode of schizophrenia can be answered with confidence. Until such studies have been conducted, clinicians should prioritize relapse prevention, particularly in the early years of illness, by encouraging indefinite, continuous antipsychotic treatment, and avoid unnecessary side-effects by using the lowest possible effective dose and selecting the best tolerated antipsychotic.